2021
DOI: 10.1186/s12957-021-02124-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially methylated genes as diagnostic and prognostic biomarkers of breast cancer

Abstract: Background Aberrant DNA methylation is significantly associated with breast cancer. Methods In this study, we aimed to determine novel methylation biomarkers using a bioinformatics analysis approach that could have clinical value for breast cancer diagnosis and prognosis. Firstly, differentially methylated DNA patterns were detected in breast cancer samples by comparing publicly available datasets (GSE72245 and GSE88883). Methylation levels in 7 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Among them, the incidence of postmenopausal women ranging from 40 to 60 years old is higher [ 3 ]. Similar to a few types of tumors, such as thyroid cancer, the natural development of breast cancer is usually long, and it takes 7 to 8 years for the tumor to reach a sphere with a diameter of 1 cm [ 4 ]. Moreover, surgical treatment is the main therapy for breast cancer, and radiotherapy is one of the local treatment methods [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the incidence of postmenopausal women ranging from 40 to 60 years old is higher [ 3 ]. Similar to a few types of tumors, such as thyroid cancer, the natural development of breast cancer is usually long, and it takes 7 to 8 years for the tumor to reach a sphere with a diameter of 1 cm [ 4 ]. Moreover, surgical treatment is the main therapy for breast cancer, and radiotherapy is one of the local treatment methods [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that 22.4% (11 out of 49) of the benign tumor samples tested positive for PCDHB15 methylation supports these hypotheses; however, further clinical analysis using a larger sample size and different molecular subtypes will be required to demonstrate whether PCDHB15 methylation is involved in the field defect of breast cancer (36). The sensitivity of PCDHB15 methylation (40.8%) in breast cancer detection in serum would not allow its use as a sole biomarker; however it could potentially serve as one epigenetic biomarker in a 'methylation signature panel' for the diagnosis and/or prognosis of breast cancer (37)(38)(39). Previous studies have identified distinct methylation biomarkers indicating the signaling-mediated epigenetic silencing of tumor suppressors, regardless of different subtypes of breast (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of PCDHB15 methylation (40.8%) in breast cancer detection in serum would not allow its use as a sole biomarker; however it could potentially serve as one epigenetic biomarker in a ‘methylation signature panel’ for the diagnosis and/or prognosis of breast cancer ( 37 39 ). Previous studies have identified distinct methylation biomarkers indicating the signaling-mediated epigenetic silencing of tumor suppressors, regardless of different subtypes of breast ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, estrogen and progesterone receptor status can indicate whether a patient is suitable for endocrine therapy [ 26 ]. In contrast, traditional tumor markers are gradually showing their limitations, while novel markers at the molecular level, such as mRNA, miRNA, and DNA methylation, are being intensively investigated [ 27 30 ]. Tumor-infiltrating lymphocytes (TIL) are a heterogeneous population of lymphocytes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%